Effect of diesel injection timing on the combustion of natural gas/diesel dual-fuel engine at low-high load and low-high speed conditions. (1st January 2019) - Yousefi, Amin; Guo, Hongsheng; Birouk, Madjid
Highlights: Diesel injection timing (DIT) under different load-speed conditions was investigated. These tests were performed using a heavy-duty natural gas/diesel dual-fuel engine. Advancing DIT was found to improve thermal efficiency under all tests conditions. GHG and unburned CH4 were reduced at low load-low speed and medium load-high speed conditions. Methane emissions were increased at medium to high load-low speed conditions. Abstract: Past research has shown that advancing diesel injection timing is a promising approach to decrease the unburned methane and greenhouse gas (GHG) emissions of natural gas/diesel dual-fuel engines at lower engine loads. However, this benefit may not persist under medium to high load-low speed conditions. To explore this, the present paper uses experiments and detailed computational fluid dynamic (CFD) modeling to investigate the impacts of diesel injection timing on the combustion and emissions performance of a heavy-duty natural gas/diesel dual-fuel engine under four different engine load-speed conditions. The results showed that advancing diesel injection timing increases the peak pressure, thermal efficiency, and NOx emissions for all examined engine load-speed conditions. Advancing diesel injection timing also significantly decreases the unburned methane and CO2 -equivalent (GHG) emissions of the dual-fuel engine under low load-low speed and medium load-high speed conditions. The concentration of OH and CH4 revealed that the central part of the combustion chamber is the main source of the unburned methane emissions under low load-low speed and medium load-high speed conditions, and advancing diesel injection timing significantly improves the combustion of natural gas-air mixture in this region. However, advancing diesel injection timing slightly increases the unburned methane emissions trapped in the crevice volume. However, this slight increase in the unburned methane emissions in the crevice volume is much lower than its significant decrease in the central region of the combustion chamber. At medium to high load-low speed conditions, there is almost no unburned methane in the central part of the combustion chamber, and the crevice region is considered as the main source of unburned methane emissions. As a result, advancing diesel injection timing does not improve the combustion of natural gas-air mixture in the central part of the combustion chamber but slightly increases the unburned methane trapped in the crevice region. This is the main reason that advancing diesel injection timing slightly increases the unburned methane emissions under medium to high load-low speed conditions. Overall, advancing diesel injection timing significantly increases thermal efficiency and decreases the unburned methane and GHG emissions under low load-low speed and medium load-high speed conditions. It improves the thermal efficiency under medium to high load-low speed conditions, but comes at the expense of increased methane and unchanged GHG emissions.